Analisis Pengaruh Jumlah Pelat Helical Terhadap Kapasitas Daya Dukung Lateral Pondasi Helical Pada Tanah Gambut - Rio Hidayat; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Helical pile can provide an alternative for wood pile over peat soil. The reaserch studied about the effect of amount of helical plates to lateral capacity of helical pile and compared to wood pile and helical without pile. The amount of helical plates used were L, 2L, 3L, LM, and LMS with spacing 50cm. Lateral ultimate capacity was interpreted by Tangent Intersection and. Theoritical lateral capacity of helical pile was calculated using Broms method. Data obtained from experiments in the form of load and displacement described in the normal scale and interpreted by using method tangen of intersection. It is known that increasing the addition of the same diameter of helical plate will increase the lateral bearing capacity of helical pile. But if the bottom of helical plate is smaller then the addition of helical plate no significant effect on the lateral bearing capacity although the helical plate on it larger.Loading experimental results were compared with the result of calculation lateral bearing capacity used Broms method. From the comparison note the lateral bearing capacity of the field is greater than analytical lateral bearing capacity.Keywords: Helical Pile, amount of Helical Plates, Peat soil, lateral Capacity, Wood Pile, pile without helical.